Analysis Mathematical Problem Solving Ability of Assimilator Student: Kolb Learning Style - Ade Kumalasari; Sri Winarni; Rohati Rohati; Marlina Marlina; Mersya Gusti Aulia (Program Studi Tadris Matematika IAIN Salatiga, 2022)
Student learning styles affect the problem-solving abilities. Therefore, further studies on student learning styles are needed regarding problem solving abilities. This research aims to analyze students' problem-solving ability with assimilator learning styles. This research is qualitative research using descriptive method. The subjects of this study were two students of class XI MIPA 1 SMA Adhyaksa 1 Jambi City. The students in question are students with assimilator learning styles. The instruments used were Kolb's learning style questionnaire, mathematical problem-solving ability tests, and interview guidelines. Based on the results of tests and interviews on the subject, it was found that, in general, not all indicators of problem-solving abilities can be met by students with assimilator learning styles. However, they are good at formulating, planning, and implementing problem solving. However, not by checking again. In formulating the problem, students do not write it on the answer sheet but can explain it well during the interview. The tendency of students to solve problems theoretically causes students to have difficulty when they do not know the formula to solve the problem.